Level and conditions of selected co-ordination and jumping abilities among advanced water-polo players - Garbolewski, K.; Starosta, W. (Journal of Human Kinetics, 2002)
Water-polo is considered as complex sport discipline. Players are required to have a high level of fitness and co-ordination abilities. Among fitness abilities there are strength, velocity and endurance, which are the basics of tactical actions and techniques. A general overview of motor abilities requires considering different coordination abilities, which level and conditions have not been researched completely. The potential of co-ordination is manifested in every movement, and it determines players` possibilities assigning their present condition of fitness workout. Therefore, it is justified to undertake research of various aspects of motor coordination. The objective of the research was to determine the level and dependence of the selected co-ordination and jumping abilities among advanced water-polo players of different age groups: 11 young juniors, 11 juniors, 13 seniors (Polish national team), 10 seniors (German champions). The authors used Starosta coordination and jumping tests (1978a, 1978b) in order to establish the level of motor co-ordination and jumping abilities. On the basis of the gathered material it was observed that juniors had the highest level of the selected co-ordination and jumping abilities. There were no significant relationships between motor co-ordination and jumping abilities. Besides, it was established that there were no significant relationships among the results of motor co-ordination and jumping abilities and somatic indexes. Having tested motor co-ordination, it was proved that left turns are the dominant ones among the majority of water-polo players.